Immigration and trade in Portugal : a static and dynamic panel data analysis - Faustino, Horácio C. (2010)
This article tests the relation between immigration and Portuguese bilateral trade, considering the fifteen European partners (EU15). Using a static and dynamic panel data analysis, the results show that the stock of immigrants has a positive effect on Portuguese exports, imports and bilateral intra-industry trade. These results suggest that immigration affects all types of trade in a positive way. The underlying assumption is that immigration contributes to decrease the costs of transactions, which in turn promotes all trade flows. The static and dynamic results do not confirm the hypothesis of a negative effect of immigration on Portuguese exports. In the static model, a 10% increase in immigration induces a 5.98 % increase in exports and a 5.55% increase in imports. The effect on the Portuguese trade balance is positive. However, the dynamic results for the export and import equations are more reliable, showing a smaller positive effect on exports. A 10% increase in bilateral immigration induces a 0.47% and 2.34% increase in exports and imports, respectively. Our findings also suggest that when immigrants to Portugal originate from a Latin partner-country, the effects on trade are stronger than in the case of immigrants from non-Latin countries. The study is based on an extended gravitational model, in order to incorporate the qualitative factors as control variables.